Development and validation of the high performance liquid chromatography–ion exclusion method for detection of lactic acid in milk - Milagres, Maria Patricia; Brandão, Sebastião César Cardoso; Minim, Valéria Paula Rodrigues; Minim, Luis Antonio; Magalhães, Mirella Araujo (Food Chemistry, 2012)
The present work reports the development and validation of an analytical method for lactic acid quantification in milk by ion exclusion–HPLC with UV detection. This method showed good precision (variation coefficient <7.0%) and good accuracy (97.6–99.6%). Calibration curves were linear (R2 > 0.996) at the tested range of 5.0–25.0 mmol L−1; and the detection and quantification limits were 0.5 and 1.0 mmol L−1, respectively. Analysis of lactic acid in fermented milk (FM) or NaOH neutralised fermented milk (FNM) was performed using samples obtained during 9 h of fermentation. An ANOVA analysis combined with the Tukey test was used to show that the method was insensitive to the differences between FM and FNM. The proposed method therefore proved to be a useful quality control tool in laboratories because it was able to determine milk acidity even in adulterated samples.
Keywords: Method development; Method validation; Ion exclusion; High-performance; liquid chromatography; Lactic acid; Milk